B-cell-specific MhcII regulates microbiota composition in a primarily IgA-independent manner - Roland, Mary Melissa; Peacock, Tori E.; Hall, Nia; Mohammed, Ahmed Dawood; Ball, Ryan; Jolly, Amy; Alexeev, Sergei; Dopkins, Nicolas; Nagarkatti, Mitzi; Nagarkatti, Prakash; Kubinak, Jason L. (Frontiers in Immunology, 2023)
MhcII-mediated coordination of cellular interactions determines the capacity of an individual's adaptive immune response to serve as a force of natural selection regulating microbial ecology in the gut. However, despite representing more than 95% of the MhcII-expressing cells in secondary lymphoid tissues (SLOs), direct assessment of the role of B-cell-specific MhcII signaling in the regulation of gut microbial ecology has not been empirically tested. Here, we present the results of a novel Rag1 -/-adoptive transfer model our group has developed to address this gap in our knowledge. Results from our experiments demonstrate that B-cell-specific MhcII regulates phylogenetic composition, species abundance, and species richness in gut microbial communities. However, contrary to expectations, this effect appears to be primarily driven in an IgA-independent manner.